Chemistry of polyhalogenated nitrobutadienes, 17: Efficient synthesis of persubstituted chloroquinolinyl-1H-pyrazoles and evaluation of their antimalarial, anti-SARS-CoV-2, antibacterial, and cytotoxic activities - Zapol’skii, Viktor A.; Berneburg, Isabell; Bilitewski, Ursula; Dillenberger, Melissa; Becker, Katja; Jungwirth, Stefan; Shekhar, Aditya; Krueger, Bastian; Kaufmann, Dieter E. (Beilstein Journal of Organic Chemistry, 2022)
A series of 26 novel 1-(7-chloroquinolin-4-yl)-4-nitro-1H-pyrazoles bearing a dichloromethyl and an amino or thio moiety at C3 and C5 has been prepared in yields up to 72% from the reaction of 1,1-bisazolyl-, 1-azolyl-1-amino-, and 1-thioperchloro-2-nitrobuta-1,3-dienes with 7-chloro-4-hydrazinylquinoline. A new way for the formation of a pyrazole cycle from 3-methyl-2-(2,3,3-trichloro-1-nitroallylidene)oxazolidine (6) is also described. In addition, the antimalarial activity of the synthesized compounds has been evaluated in vitro against the protozoan malaria parasite Plasmodium falciparum. Notably, the 7-chloro-4-(5-(dichloromethyl)-4-nitro-3-(1H-1,2,4-triazol-1-yl)-1H-pyrazol-1-yl)quinoline (3b) and 7-chloro-4-(3-((4-chlorophenyl)thio)-5-(dichloromethyl)-4-nitro-1H-pyrazol-1-yl)quinoline (9e) inhibited the growth of the chloroquine-sensitive Plasmodium falciparum strain 3D7 with EC50 values of 0.2 ± 0.1 µM (85 ng/mL, 200 nM) and 0.2 ± 0.04 µM (100 ng/mL, 200 nM), respectively. Two compounds (3b and 10d) have also been tested for anti-SARS-CoV-2, antibacterial, and cytotoxic activity.
Keywords: antimalarial activity; anti-SARS-CoV-2 activity; chloroquine; 2-nitroperchlorobutadiene; nucleophilic vinylic substitution; 1H-pyrazoles

World malaria report 2019 (World Health Organization, 2019)

(untitled) - Ridley, R. G. (Nature, 2002)

(untitled) - Satarker, S.; Ahuja, T.; Banerjee, M.; E, V. B.; Dogra, S.; Agarwal, T.; Nampoothiri, M. (Curr. Pharmacol. Rep., 2020)

(untitled) - Costanzo, M.; De Giglio, M. A. R.; Roviello, G. N. (Curr. Med. Chem., 2020)

(untitled) - Geleris, J.; Sun, Y.; Platt, J.; Zucker, J.; Baldwin, M.; Hripcsak, G.; Labella, A.; Manson, D. K.; Kubin, C.; Barr, R. G.; Sobieszczyk, M. E.; Schluger, N. W. (N. Engl. J. Med., 2020)

(untitled) - Bauman, J. L.; Tisdale, J. E. (Pharmacotherapy, 2020)

(untitled) - Ianevski, A.; Yao, R.; Fenstad, M. H.; Biza, S.; Zusinaite, E.; Reisberg, T.; Lysvand, H.; Løseth, K.; Landsem, V. M.; Malmring, J. F.; Oksenych, V.; Erlandsen, S. E.; et al. (Viruses, 2020)

(untitled) - Kaberdin, R. V.; Potkin, V. I.; Zapol'skii, V. A. (Russ. Chem. Rev., 1997)

(untitled) - Zapol’skii, V. A.; Bilitewski, U.; Kupiec, S. R.; Ramming, I.; Kaufmann, D. E. (Molecules, 2020)

(untitled) - Haeussler, K.; Berneburg, I.; Jortzik, E.; Hahn, J.; Rahbari, M.; Schulz, N.; Preuss, J.; Zapol’skii, V. A.; Bode, L.; Pinkerton, A. B.; Kaufmann, D. E.; Rahlfs, S.; et al. (Malar. J., 2019)

(untitled) - Zapol'skii, V. A.; Namyslo, J. C.; Sergeev, G.; Brönstrup, M.; Gjikaj, M.; Kaufmann, D. E. (Eur. J. Org. Chem., 2015)

(untitled) - Meyer, C.; Zapol’skii, V. A.; Adam, A. E. W.; Kaufmann, D. E. (Synthesis, 2008)

(untitled) - Zapol'skii, V. A.; Yang, X.; Namyslo, J. C.; Gjikaj, M.; Kaufmann, D. E. (Synthesis, 2012)

(untitled) - Zapol'skii, V. A.; Namyslo, J. C.; Gjikaj, M.; Kaufmann, D. E. (Heterocycles, 2016)

(untitled) - Badran, A.-S.; El‐Gohary, N. M.; Ibrahim, M. A.; Hashiem, S. H. (J. Heterocycl. Chem., 2020)

(untitled) - Fathalla, O. A.; Zaki, M. E. A.; El Hefny, E. A.; Swelam, S. A. (Int. J. Pharm. (Hyderabad, India), 2012)

(untitled) - Aggarwal, R.; Kumar, V.; Singh, S. P. (Indian J. Chem., Sect. B: Org. Chem. Incl. Med. Chem., 2006)

(untitled) - Singh, S. P.; Tarar, L. S.; Vaid, R. K.; Elguero, J.; Martínez, A. (J. Heterocycl. Chem., 1989)

(untitled) - Cunico, W.; Cechinel, C. A.; Bonacorso, H. G.; Martins, M. A. P.; Zanatta, N.; de Souza, M. V. N.; Freitas, I. O.; Soares, R. P. P.; Krettli, A. U. (Bioorg. Med. Chem. Lett., 2006)

WO Pat. Appl. - Grant, E. B., III (9-Alkyl- and 9-Alkylidenyl-6-O-Alkyl-11,12-Carbamate-Ketolide Antimicrobials, 2006)

(untitled) - Hernández-Vázquez, E.; Castañeda-Arriaga, R.; Ramírez-Espinosa, J. J.; Medina-Campos, O. N.; Hernández-Luis, F.; Chaverri, J. P.; Estrada-Soto, S. (Eur. J. Med. Chem., 2015)

(untitled) - Thomas, J. B.; Giddings, A. M.; Wiethe, R. W.; Olepu, S.; Warner, K. R.; Sarret, P.; Gendron, L.; Longpre, J.-M.; Zhang, Y.; Runyon, S. P.; Gilmour, B. P. (J. Med. Chem., 2014)

Eur. Pat. Appl. - Kurahashi, Y.; Moriya, K.; Sawada, H.; Sakuma, H.; Watanabe, R.; Ito, A. (Microbicidal Quinoline Derivatives, 1996)

(untitled) - Patil, S.; Sharma, R. (Int. J. PharmTech Res., 2014)

(untitled) - Zapol’skii, V. A.; Namyslo, J. C.; de Meijere, A.; Kaufmann, D. E. (Beilstein J. Org. Chem., 2012)

(untitled) - Zapol’skii, V. A.; Namyslo, J. C.; Altug, C.; Gjikaj, M.; Kaufmann, D. E. (Synthesis, 2008)

(untitled) - Zapol’skii, V. A.; Namyslo, J. C.; Gjikaj, M.; Kaufmann, D. E. (Z. Naturforsch., B: J. Chem. Sci., 2010)

(untitled) - Katritzky, A. R.; Lan, X.; Yang, J. Z.; Denisko, O. V. (Chem. Rev., 1998)

(untitled) - Ibis, C.; Sayil, M. C.; Deniz, N. G. (Acta Crystallogr., Sect. E: Struct. Rep. Online, 2006)

(untitled) - Sergeev, G.; Roy, S.; Jarek, M.; Zapolskii, V.; Kaufmann, D. E.; Nandy, R. K.; Tegge, W. (BMC Microbiol., 2014)

Eur. Pat. Appl. - Singh, M.; Kaufmann, D.; Zapol‘skii, V.; Oehlmann, W. (4-Nitro-5-dichloromethylpyrazol derivatives fort he treatment of infectous diseases, 2015)

(untitled) - Bürgi, M.; Zapol’skii, V. A.; Hinkelmann, B.; Köster, M.; Kaufmann, D. E.; Sasse, F.; Hauser, H.; Etcheverrigaray, M.; Kratje, R.; Bollati-Fogolín, M.; Oggero, M. (J. Biotechnol., 2016)

(untitled) - Bolger, G.; Roy, S.; Zapol'skii, V. A.; Kaufmann, D. E.; Schnürch, M.; Mihovilovic, M. D.; Nandy, R. K.; Tegge, W. (J. Med. Microbiol., 2016)

(untitled) - Zapol’skii, V. A.; Fischer, R.; Namyslo, J. C.; Kaufmann, D. E. (Bioorg. Med. Chem., 2009)

(untitled) - Ekland, E. H.; Schneider, J.; Fidock, D. A. (FASEB J., 2011)

(untitled) - Kasozi, D.; Mohring, F.; Rahlfs, S.; Meyer, A. J.; Becker, K. (PLoS Pathog., 2013)

(untitled) - Akoachere, M.; Buchholz, K.; Fischer, E.; Burhenne, J.; Haefeli, W. E.; Schirmer, R. H.; Becker, K. (Antimicrob. Agents Chemother., 2005)

(untitled) - Kasozi, D. M.; Gromer, S.; Adler, H.; Zocher, K.; Rahlfs, S.; Wittlin, S.; Fritz-Wolf, K.; Schirmer, R. H.; Becker, K. (Redox Rep., 2011)

(untitled) - Rahbari, M.; Rahlfs, S.; Jortzik, E.; Bogeski, I.; Becker, K. (PLoS One, 2017)